Determining the Factors Effecting Raw Material Preference in Furniture Sector in Turkey and the Problems Experienced in Supplying and Marketing Raw Materials - Aydın, Aytaç; Nemli, Gökay; Gündüz, Gökhan (My University, 2019)
Furniture industry is one of the oldest and a developed industry in Turkey. In the last 20-25 years of furniture industry, in addition to production for the country’s need, Turkey started to produce for export, to work technology-supported and to make large scale mass production rather than local workplace production. In addition to that, investments for innovative and technological production have been increasing to make production more efficient and high-quality. The scope of this study is to identify the factors that affect the raw material choices of the businesses active in furniture industry in Turkey and to determine the problems encountered in supplying raw material and in marketing. The study data were obtained by the survey method. Survey application was carried out in 283 businesses which were chosen through sampling among 20,867 businesses active all-around Turkey. The questionnaires applied by face to face interview technique were transferred to computer environment and analyzed with MS Excel and SPSS programs. Descriptive statistics and chi-square were used in the analyzes. It was found that the businesses in furniture industry were structured as single person company, which mainly make order production and mostly they produce household furniture. It was seen that mostly MDF, particleboard and plywood were used in the sector and this is mostly due to the clients’ choice. Among the outstanding problems were high raw material prices, low quality of these materials, lack of customer's material knowledge and high production expenses. It was also found that lacquer paint and varnish were preferred as coating materials due to their decorative look.
Keywords: İşletme; Malzeme Bilimleri; Kâğıt ve Ahşap; İktisat